Philippe van Snick : Pans de sensation - Gelder, Hilde Van; Gildemyn, Marie-Pascale (Leuven Acco, 2009)
This cahier documents an artistic intervention undertaken by Philippe Van Snick over the course of two years (2005-2007) in a contemporary studio at Kesselsstraat 14 in Schaarbeek. The project commenced with the colors inherent to Philippe Van Snick's work: the three primary colors, the three secondary colors, black, and white. The colors were mixed with white and applied on eight different rectangular planes. Then these colors were progressively mixed with black. Blue and black, symbols of day and night, remained unaltered within the architectural framework throughout the process, as two vertical rectangular surfaces. Gold and silver were added in the form of two cubes. This combination restored the color palette the artist has been using since the early 1980s. Finally, the different color planes were painted white.